2020
DOI: 10.1136/bmjmilitary-2019-001373
|View full text |Cite
|
Sign up to set email alerts
|

Humeral shaft fracture and radial nerve palsy in Korean soldiers: focus on arm wrestling related injury

Abstract: IntroductionHumeral shaft fractures can lead to radial nerve injury and may require surgery and rehabilitation. We determined the causative events of humeral fracture, including arm wrestling, in young Korean soldiers and examined whether humeral fracture is related to demographic characteristics and the presence of radial nerve palsy.MethodsWe reviewed 7.5 years (July 2012 to June 2019) of medical records covering patients who had experienced a humeral shaft fracture after entering military service and had re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(39 citation statements)
references
References 21 publications
2
31
0
Order By: Relevance
“…subscapularis, pectoralis, and latissimus dorsi muscles in the shoulder, which are resisted by an opponent's external rotation force or another counter force [7]. Also, forceful elbow flexion and shoulder internal rotation may lead to fracture of a spiral nature have been reported in the literature [8,9]. According to some authors, pure rotator force without axial load on the humerus causes spiral fracture only, while axial load and rotator force can cause a butterfly fragment [10].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…subscapularis, pectoralis, and latissimus dorsi muscles in the shoulder, which are resisted by an opponent's external rotation force or another counter force [7]. Also, forceful elbow flexion and shoulder internal rotation may lead to fracture of a spiral nature have been reported in the literature [8,9]. According to some authors, pure rotator force without axial load on the humerus causes spiral fracture only, while axial load and rotator force can cause a butterfly fragment [10].…”
Section: Resultsmentioning
confidence: 99%
“…The patients with humerus fracture ranged in age from 22 to 48-years-old, average of 31.2 years [12]. Also, it was reported that the cases mean (± SD) age was 21.7 ± 3.9 years in another study [9].…”
Section: Age Range Of Casesmentioning
confidence: 92%
See 3 more Smart Citations